Digital Marketing Sebagai Strategi Pemasaran Dan Pemberdayaan Ekonomi Lokal Pada IPNU IPPNU Di Desa Mancilan - Airlangga, Primaadi; Hariono, Tholib; Sufaidah, Siti; Khafidhoh, Nur; Munawarah, Munawarah; Zulfikar, Zulfikar; Lestari, Devina Ayu; Ainun Oktafiani, Alfi; Nurdin Halidi, Idris; Miftahul Ulum, Adip; Ahmad Saiful, Basalaf (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
IPNU IPPNU is a social institution that is a forum for youth that develops awareness and social responsibility towards productive youth. IPNU and IPPNU in Mancilan Village are one of the pillars of youth organizations followed by the wider community who are faced with a number of problems. From the results of pre-program identification, several problems faced by partners were found. The first problem is that the implementation of organizational management is not running well so that many organizational programs are not running optimally. The main obstacle faced is limited funds to carry out various activities aimed at achieving the organization's vision and mission. Currently, their main source of funding is membership fees, which are not always sufficient to support all the initiatives they undertake. With this background, the service team conducted training in understanding digital marketing in Mojoagung District, Mancilan Village, Jombang Regency. This service is carried out to increase sales efforts by utilizing digital platforms. Writing skills in marketplace media are very important for increasing brand awareness for potential consumers. The problem that partners have is that partners have not been able to create captions, taglines, descriptions for products that will be marketed online. Apart from that, regarding digital marketing planning, the service team brought in a resource person, one of the practitioners managing Jombang students' official Instagram accounts, to provide material related to digital marketing. This service activity uses the CBL (Community Based Learning) approach which integrates the involvement of a community in learning consisting of copywriting and digital marketing planning techniques. Then continue creating content that can be uploaded directly to partner social media.